Penelusuran Jejak Karbon: Implementasi Pembelajaran Kontekstual Berbasis Literasi dan Numerasi Sains untuk Meningkatkan Kesadaran Lingkungan pada Siswa SMP: (Implementation of Contextual-based Science Literacy and Numeracy Learning: Carbon Footprint Tracing to Raise Students’ Environmental Awareness) - Azizah, Lutfia; Nadhif Tsalist, Farhah; Priska Ardyanti, Vicensia; Siswandari, Puti (BIODIK, 2026)
Students' understanding of climate change is crucial for developing pro-environmental behaviors. However, studies on climate change understanding based on science literacy and numeracy are still limited. This study aims to analyze students' understanding of climate change based on the context of science literacy and numeracy. The participants were 24 ninth-grade students. Students' understanding of climate change in the context of science was assessed using an open-ended survey that had been validated through expert judgement. The data were analyzed using the percentage of students' answers. In the context of literacy, the results showed that 35.8% of students believed that climate change was caused by the use of energy from fossil fuels, and 50% of students recognized its impact on ecosystems and extreme weather. Up to 67% of students stated that adopting pro-environmental habits including walking, taking public transportation, and shutting off electronics when not in use contributes to its prevention. In the context of numeracy, students can calculate their carbon footprint and understand its meaning, but only 20% were able to interpret numerical data. These findings indicate the need to strengthen contextual science learning based on numeracy so that students can understand data-based concepts. The implementation of science learning based on contextual literacy and numeracy based on data can encourage students' knowledge about the impact of climate change and their intention towards pro-environmental behavior. Abstrak. Pemahaman siswa tentang perubahan iklim penting untuk menjaring sikap ramah lingkungan mereka. Namun, kajian pemahaman perubahan iklim berdasarkan literasi dan numerasi sains masih terbatas. Penelitian ini bertujuan untuk menganalisis pemahaman siswa mengenai perubahan iklim berdasarkan literasi dan numerasi sains. Partisipan terdiri atas 24 siswa kelas 9 SMP. Pemahaman siswa tentang perubahan iklim dijaring menggunakan open-ended survey dan dianalisis dengan persentase kategorisasi jawaban. Pada konteks literasi, hasil menunjukkan bahwa 35,8% siswa berpendapat perubahan iklim akibat penggunaan energi dari bahan bakar fosil dan 50% siswa mengenali dampaknya terhadap ekosistem dan memicu cuaca ekstrem. Sebanyak 67% siswa menyatakan bahwa sikap ramah lingkungan seperti berjalan kaki, menggunakan transportasi umum, dan mematikan alat elektronik saat tidak digunakan adalah bentuk kontribusi terhadap pencegahan perubahan iklim. Pada konteks numerasi, siswa dapat menghitung jejak karbon dengan benar dan mengerti maknanya. Akan tetapi, hanya 20% siswa yang mampu menginterpretasikan data numerik. Temuan ini mengindikasikan perlunya penguatan pembelajaran sains kontekstual berbasis numerasi sehingga siswa dapat memahami konsep berbasis data. Implementasi pembelajaran sains berbasis literasi dan numerasi kontekstual berdasarkan data dapat mendorong pengetahuan siswa tentang dampak perubahan iklim dan niat untuk berperilaku ramah lingkungan.